Efectos de la violencia de pareja en mujeres migrantes. (2013)
This study analyzes the relationship between partner violence; depression and maternal self-efficacy in migrant women. It is thought that this type of violence brings about sinking morale and a hindrance for their development as mothers. It is a quantitative study of an explanatory correlational type; worked with 40 immigrant women with a residence of two to 25 years; with at least one reported episode of violation and at least one son in preschool. Three instruments were employed: The Parental Involvement and Efficacy ; The Survey-Depression Scale and The Revised Conflict Tactic Scale . The results showed important relationships between the variables; namely; the more violence women suffer; the greater the depression is; and the greater the depression is; the lesser the maternal self-efficacy becomes.